Perspectives on Agmatine Neurotransmission in Acute and Chronic Stressrelated Conditions - Hassanshahi, Amin; Soti, Monavareh; Ranjbar, Hoda; Razavinasab, Moazamehosadat; Pirmoradi, Zeynab; Kohlmeier, Kristi A.; Janahmadi, Mahyar; Shabani, Mohammad (Mini Reviews in Medicinal Chemistry, 2023)
Adaptive responses to stressful stimuli in the environment are believed to restore homeostasis after stressful events. Stress activates the hypothalamic-pituitary-adrenocortical (HPA) axis, which releases glucocorticoids (GCs) into the bloodstream. Recently, agmatine, an endogenous monoamine was discovered to have the potential as a pharmacotherapy for stress. Agmatine is released in response to certain stress conditions, especially those involving GCs, and participates in establishing homeostasis disturbed by stress following GC activation. The therapeutic potential of agmatine for the management of psychological diseases involving stress and depression is promising based on a significant amount of literature. When exogenously applied, agmatine leads to reductions in levels of GCs and counteracts stress-related morphologic, synaptic, and molecular changes. However, the exact mechanism of action by which agmatine modifies the effects resulting from stress hormone secretion is not fully understood. This review aims to present the most possible mechanisms by which agmatine reduces the harmful effects of chronic and acute stress. Several studies suggest chronic stress exposure and repeated corticosteroid treatment lower agmatine levels, contributing to stress-related symptoms. Agmatine acts as an antistress agent by activating mTOR signaling, inhibiting NMDA receptors, suppressing iNOS, and maintaining bodyweight by activating α-2adrenergic receptors. Exogenous administration that restores agmatine levels may provide protection against stress-induced changes by reducing GCs release, stimulating anti-inflammatory processes, and releasing neuroprotective factors, which are not found in all therapies currently being used to treat stress-related disorders. The administration of exogenous agmatine should also be considered a therapeutic element that is capable of triggering a neural protective response that counters the effects of chronic stress. When combined with existing treatment strategies, this may have synergistic beneficial effects.
Keywords: chronic stress